Preliminary Investigations on the Distribution of Leptospira Serovars in Domestic Animals in North‐west Morocco. Issue 2 (26th July 2014) - Benkirane, A.; Noury, S.; Hartskeerl, R. A.; Goris, M. G. A.; Ahmed, A.; Nally, J. E.
Summary: Leptospirosis is a neglected zoonosis of global importance with a complex epidemiology that affects humans, domestic and wild mammals. However, due to the diversity of clinical signs and difficulties of establishing a confirmatory laboratory diagnosis, the disease remains poorly investigated, particularly in the developing world. In Morocco, a descriptive study of the seroprevalence of Leptospira infection in animals has never been undertaken. To fill this gap, the current study was conducted on a subset of animals in north‐west Morocco as a preliminary step towards understanding the epidemiological patterns of animal leptospirosis in the country. The study was conducted on 289 serum samples collected between January and April 2012 from dogs, cattle, sheep, goats and donkeys in the areas of Rabat‐Temara, Sidi Kacem and Oulmes. All serum samples were tested by the MAT with 14 reference strains of the most prevalent pathogenic serovars of Leptospira and two serovars of non‐pathogenic Leptospira . The overall seroprevalence of Leptospira in cattle, sheep, goats, dogs and donkeys was 15%, 18%, 20%, 21% and 20%, respectively. The most prevalent serogroups found in each species were Ballum, Sejroe, and Australis in cattle, Ballum, Australis and Sejroe in sheep, Australis and Ballum in goats, Javanica and Australis in donkey and Australis, Ballum and Canicola in dogs. Of all the serogroups tested in this study, Icterohaemorrhagiae, the only serogroup which has been previously reported in humans in Morocco, was rarely reactive. The majority of reactive sera were collected from low land areas. A large number of sera samples classified as seronegative when tested against pathogenic leptospires were positive when tested against non‐pathogenic leptospires; this is suggestive of possible novel, as yet unclassified, Leptospira serovars in Morocco. Eleven of thirteen sheep urine samples were positive by real‐time PCR confirming their role as Leptospira carriers in Morocco.